DIGITAL VULNERABILITIES: CYBERSECURITY THREATS IN INDIA’S DIGITAL TRANSFORMATION JOURNEY - Kumar, Saurabh; Bansal, Garima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is becoming a worldwide leader in digital innovation as aoutcome of the fast digital revolution that has followed in the country. This change has resulted in enormous financial and community improvements. With that actuality said, this advancement has also brought to light significant vulnerabilities inside the digital economy. This paper examines the cybersecurity threats inherent in India’s digital transformation journey, focusing on emerging challenges, such as cyberattacks on critical infrastructure, data breaches, and vulnerabilities in the growing digital payment systems. It highlights the interplay between technological adoption, regulatory frameworks, and public awareness in mitigating cyber risks. By analyzing case studies and contemporary data, the study underscores the urgency for a robust cybersecurity infrastructure and policy framework. The findings advocate for a multi-stakeholder approach involving government, private entities, and individuals to secure India’s digital future while maintaining the pace of innovation and inclusivity.